35 Frictionless digital referral management – the key to implementing novel care pathways. (12th November 2018) - Mahapatra, Piyush; Prinsloo, Francois; Lykostratis, Harry; Ferran, Nicholas
Abstract : We describe a clinician-led transformation of trauma and orthopaedics services in one of the country's largest integrated healthcare trusts. Analysis of 2638 outpatient surgical procedures showed an unacceptable delay (mean=16.1 days) from injury to surgical treatment. A 5 year retrospective review of trust litigation cases yielded 28 litigation cases related to failure/delay of treatment or diagnosis for traumatic injuries with resultant total claims of £2, 000, 000. A novel N3-network hosted cloud-based bespoke single-point referral management system was developed. Referrals are processed at a specialist-led Virtual Fracture Clinic (VFC) with patients allocated to specific digitally actioned treatment pathways. Key stakeholders including referrers, assessors and treatment providers were involved from the early stages of system design. Regular on-platform feedback is obtained for quality control and iterative improvements. 11 769 patients have been assessed in VFC since March 2017. Post-implementation, 720 outpatient surgical procedures were performed with a significant reduction in mean time from injury to treatment (9.6 days). The British Orthopaedic Association target of <72 hours from referral to assessment was achieved in 88.7% of cases. 25.4% of referrals were deemed to not require a face-to-face (F2F) appointment. 67% of assessors felt that VFC reduces F2F appointments and is overall beneficial. 90% of patients that were discharged without a F2F appointment were positive or neutral about the service. 77% of referrers felt the system was safer for patients and 71% felt that it was an overall improvement. Cost analysis showed a £1 04 576 cost saving in addition to perceived further litigation-related savings. Frictionless digital referral management and virtual clinical pathways can improve patient care and help manage increasing workload pressures whilst simultaneously reducing costs and maintaining stakeholder satisfaction.